Antioxidant activity of plants methanolic extracts from UiTM Pahang Forest Reserve / Liliwirianis Nawi …[et al.] - Nawi, Liliwirianis; Musa, Nor Lailatul Wahidah; Wan Mohd Zain, Wan Zuraida; Karim, Shaikh Abdul; Kassim, Jamaluddin (2010)
Antioxidants are important substances that help to reduce the formation of free radicals that give deleterious effect to human body. This study was conducted to determine in vitro evaluation on the antioxidant activity of Melastoma sp. (Senduduk putih), Thottea corymbosa (Serapat), Thottea grandiflora (Hempedu beruang), Ficus sundaica (Ara), Epipremnum sp. (Pisang kera) and Smilax sp. (Rancang tembaga). To evaluate this activity, 1,1-diphenyl-2-picrylhydrazil (DPPH) method was used on six samples concentration; 50, 100, 150, 200, 250 and 500 ppm. Three control samples BHT (Butylated Hydroxyl toluene), Vitamin E and ascorbic acid (Vitamin C) were used as standard and were measured by using visible spectrometry. Result indicated that the Melastoma sp. was the highest scavenger and the lowest scavenger is the extract of Smilax sp.. Methanolic extract of Melastoma sp. had demonstrated significant free radical scavenging ability by giving IC50 values of 0.043 mg/ml (43 ppm). This indicates that Melastoma sp. is highly potential as an antioxidant source.